ASSOCIATION OF POST-TRAUMATIC GROWTH WITH THE USE OF RELIGION AND SPIRITUALITY AS A COPING STRATEGY AMONG REFUGEES OF AZAD JAMMU AND KASHMIR - Jehangir, Zarrar; Usama Bin Zubair; Syed Azhar Ali Kazmi; Anam Haider; Aroosa Burki; Anam Jamil Butt (Journal of Ayub Medical College Abbottabad, 2024)
Background: Migration under hostile circumstances and taking refuge in another country is a process which can have a great toll on mental health of the affected individuals. Religious beliefs and closeness to God could be instrumental in bringing post-traumatic growth and positive changes in one’s life after any traumatic event. This study was carried out to evaluate the association of post-traumatic growth with use of religion and spirituality as a coping strategy among refugees residing in Azad Jammu and Kashmir. Methods: In this cross-sectional study, individuals who migrated from Indian Kashmir and got settled in the Thotha refugee camp at AJK were recruited during February to April 2024 for the study. Post-traumatic growth (PTG) was assessed via post-traumatic growth inventory. Religiosity as coping strategy was measured on brief religious coping scale (Brief RCOPE). Relationship of religious coping and other socio-demographic factors was correlated with PTG among the study participants. Results: A total of three hundred and thirty participants were included in this study with mean age of 44.89±14.81. Majority of participants were male (n=237 (71.8%), married (n=260 (78.8%) and Unemployed (n=103 (31.2%). Participants who were ≤45 years old, single, employed, did not use illicit drugs and had more income had high PTG mean scores (p-value<0.05). The PTG scores of the study participants and Positive Religious coping score had positive correlation while PTG scores had negative correlation with Negative religious coping (r=-0.238, p-value <0.001). Conclusion: Post-traumatic growth was observed in individuals who were lining as refugees in camps at AJK. Individuals who were young, single, well paid and did not used illicit drugs had more chances of having PTG. Positive religious coping also increased the chances of having post-traumatic growth in individuals after migration and taking refuge in another country.